Comparative outcomes of transcatheter aortic valve replacement in bicuspid vs. tricuspid aortic valve stenosis patients: insights from the SWEDEHEART registry - Antros Louca; Petur Petursson; Joakim Sundström; Araz Rawshani; Henrik Hagström; Magnus Settergren; Stefan James; Sasha Koul; Kristofer Skoglund; Dan Ioanes; Sebastian Völz; Anna Myredal; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Limited data exist on transcatheter aortic valve replacement (TAVR) outcomes in patients with bicuspid aortic valve (BAV) stenosis. This study compared TAVR outcomes in BAV versus tricuspid aortic stenosis. Methods: This observational study included all patients who underwent TAVR in Sweden from 2016 to 2022, excluding those with pure aortic insufficiency and valve-in-valve procedures. Only Evolut-, SAPIEN-, ACURATE-, and Portico/Navitor-family devices were included. A doubly robust method was used, combining propensity score estimation and multivariable regression. Results: Among 7,095 patients, 577 (8.1 %) had BAV stenosis. The mean EUROSCORE II-predicted mortality risk was 3.8 % for BAV and 4.5 % for TAV. BAV patients were younger, predominantly male, and had fewer comorbidities but higher baseline aortic valve gradients, larger annulus diameters, and more reduced ejection fraction.After matching, 30-day mortality and all-cause mortality (median follow-up: 690 days) were similar between BAV and TAV patients (p = 0.8 for both). While BAVs had numerically lower technical success per VARC-3 criteria, this was not statistically significant (p = 0.08). However, BAV patients had lower device success (aOR = 0.8, p = 0.04) and a higher incidence of post-TAVR pacemaker implantation (aOR = 1.76, 95 % CI: 1.14–2.58, p = 0.007). No significant differences were observed in prosthesis-patient mismatch (p = 0.3), paravalvular leakage (p = 0.6), stroke (p = 0.3), or post-TAVR gradients (p > 0.9). Conclusion: TAVR in BAV patients yields similar mortality and hemodynamic outcomes as in TAV patients. However, BAVs are associated with lower device success and higher pacemaker rates. While TAVR is a viable alternative to SAVR, treatment should be individualized, especially in younger BAV patients, considering lifetime management and coronary access.